Beyond plant defense: insights on the potential of salicylic and methylsalicylic acid to contain growth of the phytopathogen Botrytis cinerea - Dieryckx, Cindy; Gaudin, Vanessa; Dupuy, Jean-William; Bonneu, Marc; Girard, Vincent; Job, Dominique (Frontiers in Plant Science, 2015)
Using Botrytis cinerea we confirmed in the present work several previous studies showing that salicylic acid, a main plant hormone, inhibits fungal growth in vitro. Such an inhibitory effect was also observed for the two salicylic acid derivatives, methylsalicylic and acetylsalicylic acid. In marked contrast, 5-sulfosalicylic acid was totally inactive. Comparative proteomics from treated vs. control mycelia showed that both the intracellular and extracellular proteomes were affected in the presence of salicylic acid or methylsalicylic acid. These data suggest several mechanisms that could potentially account for the observed fungal growth inhibition, notably pH regulation, metal homeostasis, mitochondrial respiration, ROS accumulation and cell wall remodeling. The present observations support a role played by the phytohormone SA and derivatives in directly containing the pathogen. Data are available via ProteomeXchange with identifier PXD002873.